The Role of Social-Emotional Skills in Promoting Subjective Well-Being Among Primary School Children: A Systematic Literature Review - Intan Baiduri; Farida Kurniawati; Tjut Rifameutia (Universitas Ahmad Dahlan, 2026)
This systematic review synthesizes empirical evidence on the relationship between social-emotional functioning and subjective well-being (SWB) among primary school–aged children. Following PRISMA 2020 guidelines, a comprehensive search across six databases identified three eligible quantitative studies. The findings indicate a consistent but preliminary positive association between social-emotional functioning and children’s well-being. Constructs such as emotional intelligence, social-emotional learning, and participation in organized activities were linked to dimensions of SWB, including positive affect, psychological well-being, resilience, and life satisfaction. However, the evidence base remains limited and methodologically constrained. All included studies employed cross-sectional designs and varied considerably in how social-emotional functioning was conceptualized and measured. The literature predominantly emphasizes intrapersonal competencies, while interpersonal and decision-making domains receive less attention. In addition, distinctions between individual skills and socio-contextual influences are not consistently addressed. The findings suggest that children’s well-being is shaped by multiple, interrelated pathways involving emotional competencies and social environments. Future research should adopt longitudinal designs and more coherent theoretical frameworks to better understand well-being development during middle childhood.